Analisis Efisiensi Energi pada Sistem Pengolahan Air Limbah PT. Arun LNG Lhokseumawe - Erliadi Erliadi; Ahmad Syuhada; Hamdani Hamdani (Jurnal Teknik Mesin Unsyiah, 2015)
Domestic liquid waste from residential areas of PT Arun NGL processed in Waste Water Treatment Plant. So far WWTP # 48 worked pretty well. Problems that occur in the operation of WWTP # 48 is associated with cleaner production principles are: Inefficiency of use of water; The need for clean water for residential and office buildings in the PT Arun NGL is relatively large average 700 L/capita/day, use large quantities of water have an impact on increasing the volume of domestic waste water to be generated and processed at the waste processing unit. On the other hand there has been no attempt to use effluent water WWTP # 48 whose quality is relatively good and relatively large number is 2275 m3/day. This study aimed to analyze the results of energy conservation has been done on the wastewater treatment unit at PT. Arun. To identify inefficient use of water, electricity and chlorine using gap analysis.The data observed in the field compared to the ideal condition that refers to good governance(Good Housekeeping), and then determined how much deviation. The amount of savings opportunities gained from the implementation of cleaner production in the operation of WWTP # 48 is the supply cost savings of 38%.